2022
DOI: 10.4062/biomolther.2021.078
|View full text |Cite
|
Sign up to set email alerts
|

Novel GPR43 Agonists Exert an Anti-Inflammatory Effect in a Colitis Model

Abstract: Inflammation is a type of defense response activated to protect organisms from detrimental factors, such as pathogens and tissue damage. Imbalance in inflammatory mechanisms can lead to chronic disorders, such as inflammatory bowel disease (IBD). The adaptive immune system is mainly involved in the pathogenesis of IBD, but some innate immune cells are also implicated (de Mattos et al., 2015). While many small-molecule drugs, such as aminosalicylates and corticosteroids, and biological molecules, for instance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…[96][97][98] In addition, a series of agonists of SCFA receptors can affect gut function through different mechanisms (Table 2). 66,71,[99][100][101][102] Selective GPR41 agonists are expected to become promising targets for the treatment of neurogenic diarrheal disorders because of their anti-dynamic and anti-secretory functions. 66 Selective GPR43 agonists inhibit gut transit via the PYY pathways.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…[96][97][98] In addition, a series of agonists of SCFA receptors can affect gut function through different mechanisms (Table 2). 66,71,[99][100][101][102] Selective GPR41 agonists are expected to become promising targets for the treatment of neurogenic diarrheal disorders because of their anti-dynamic and anti-secretory functions. 66 Selective GPR43 agonists inhibit gut transit via the PYY pathways.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It has been exquisitely reported that SCFA propionate could regulate immune cell differentiation through G-protein-coupled receptors (GPRs) and histone deacetylases (HDACs) ( 30 ). To explore whether propionic acid regulated Th17 and Treg cell differentiation in a GPR-dependent manner, we detected the expressions of GPR43, one of the GPRs that play an important role in the immunity and metabolism, and intracellular signaling HDAC6 ( 31 ). First, the expressions of GPR43 were increased by propionic acid stimulation under Th17 and Treg cell conditions but suppressed by using LV-shGPR43 ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…SCFAs can facilitate signaling events involving G protein-coupled receptors (GPRs), on the cell surface ( 150 , 151 ). Acetate, propionate, and butyrate are among the ligands shared by some GPRs ( 152 , 153 ). Within these receptors, we can find GPR109a (also known as hydroxycarboxylic acid receptor 2 or HCA2) expressed in the apical side of intestinal cells, adipose tissue, and immune cells ( 154 ), and in different tissues and cells of mammals can be found the free fatty acid receptor 2 (FFAR2; also known as GPR43) and the free fatty acid receptor 3 (FFAR3; also known as GPR41) ( 155 , 156 ).…”
Section: The Intestinal Microbiota In Balancementioning
confidence: 99%
“…The production of SCFAs by the gut microbiota can modulate immune cell responses ( 157 ). Different immune cells, such as neutrophils and leukocytes, predominate the expression of FFAR2 ( 158 , 159 ) and have been described to be involved in the inhibition of inflammatory pathways ( 152 , 153 ), and protective effects by diminishing the susceptibility to bacterial infections with Klebsiella pneumoniae , Citrobacter rodentium , and Staphylococcus aureus , but also by viruses such as respiratory syncytial and influenza viruses ( 159 ). Its protective effects can be compromised by inadequate fiber intake or a deficiency of FFAR2 ( 160 ).…”
Section: The Intestinal Microbiota In Balancementioning
confidence: 99%